2004
DOI: 10.2139/ssrn.533182
|View full text |Cite
|
Sign up to set email alerts
|

Buy it Now: A Hybrid Internet Market Institution

Abstract: This paper analyzes seller choices and outcomes in approximately 700 recent Internet auctions on eBay. The 'Buy it Now' option that is available in these auctions allows the seller to supplement or replace the auction with a posted price offer. We use a structural model to control for the endogenous conduct of the auction (e.g., number of bids and bidders) as well as product and seller characteristics. Among other results, we find that the 'Buy it Now' option was used more often by sellers with higher ratings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
0
31
0
1
Order By: Relevance
“…Before this recent inclusive change, many sellers were able to enter an auction with a BiN option and set the first bid so high that bidders could essentially only buy at the fixed price. Anderson et al (2004) noted that 40% of the auctions in their study with a BiN option were actually using this way to sell at a fixed price. Of the 133 auctions that were not fixed-price sales, only one ended at the BiN price.…”
Section: Selling Formatmentioning
confidence: 99%
“…Before this recent inclusive change, many sellers were able to enter an auction with a BiN option and set the first bid so high that bidders could essentially only buy at the fixed price. Anderson et al (2004) noted that 40% of the auctions in their study with a BiN option were actually using this way to sell at a fixed price. Of the 133 auctions that were not fixed-price sales, only one ended at the BiN price.…”
Section: Selling Formatmentioning
confidence: 99%
“…Therefore, we are seeking explanations which depend not on product characteristics, 9 but rather on the seller's characteristics. This differentiates our study from Anderson et al (2008), who also consider how product characteristics affect choice of auction format. Finally, we consider the situation in which the sellers choose auction formats within the same venue.…”
mentioning
confidence: 93%
“…Although several studies have found that the BIN option has a positive effect on auction price (Anderson et al 2008;Budish and Takeyama 2001;Dodonova and Khoroshilov 2004;Reynolds and Wooders 2003), others have found otherwise (Standifird et al 2005). Studies that have found a positive effect typically have been conducted in markets with high quality uncertainty, whereas those that have found no effect have been conducted in markets with low quality uncertainty.…”
Section: Buy It Nowmentioning
confidence: 99%